Pengaruh Good Governance Terhadap Kinerja Organisasi Pada Kantor Dinas Sosial Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Wajo - Andi Patotori Arismunandar; Ahmad Irza Muhafidz; Bakri Bakri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Background of this research, based on observations, highlights the high public demand for transparency and accountability in providing information, as well as the community's desire to participate in the planning and implementation of social programs, which are often overlooked. The purpose of this study is to examine the effect of good governance on organizational performance at the Office of Social Services, Population Control, Family Planning, Women's Empowerment, and Child Protection in Wajo Regency. This research adopts a survey method, where data is collected from all members of the population as the sample, totaling 65 respondents. The primary data collection technique involves questionnaires, supported by observation and documentation. The data analysis technique used is quantitative descriptive analysis. The findings indicate a positive impact of implementing good governance on the organizational performance of the aforementioned office.